Gatekeepers and Enablers: How Drug Regulators Respond to a Challenging and Changing Environment by Moving Toward a Proactive Attitude. Issue 5 (24th January 2013) - Ehmann, F; Papaluca Amati, M; Salmonson, T; Posch, M; Vamvakas, S; Hemmings, R; Eichler, H G; Schneider, C K
<x xml:space="preserve">Abstract</x> This article analyzes the role of regulatory authorities in facilitating innovation in the pharmaceutical sector. We describe how regulators are expanding their role to be not only gatekeepers but also enablers of development. They have already responded to the challenging and changing environment by moving toward a proactive attitude beyond evaluation of products, thereby more actively contributing to their development. Regulators have to continuously evolve their knowledge and standards alongside evolution in science. Creation of supportive regulatory frameworks and multistakeholder interaction will help address unmet regulatory needs. Clinical Pharmacology & Therapeutics (2013); 93 5, 425–432. doi:10.1038/clpt.2013.14